The Importance of Enhancing Critical Thinking Skill Of Pre-Service Teachers (Training and Practice : Journal of Educational Sciences, 2011)
The paper deals with the necessity of continuous work on the development of the critical thinking skill in higher education. More precisely, it aims to explain the context in which the need for teaching critical literacy to future teachers arises. The contemporary both professional and private challenges have been increased by the information and communication technology. Apart from being functionally literate teachers and students should improve the refined ability to read, write, research and communicate in a way that supports critical analysis, interpretation, processing and storing both print and non-print texts. In addition, the author discusses the possibilities of incorporating critical literacy in school curriculum, applying either implementation or teacher initiative, opting for the combination of the two (teacher competencies and governmental support). The initial teacher education must empower students not only to teach critical literacy to their own students, but also to keep developing their critical thinking skill.